2014
DOI: 10.1039/c4ee02465f
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and transient behavior in current–voltage measurements of hybrid-perovskite absorber solar cells

Abstract: This report discusses slow transient and hysteretic phenomena in perovskite-absorber solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
1,128
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,173 publications
(1,185 citation statements)
references
References 36 publications
49
1,128
4
4
Order By: Relevance
“…7b the J-V curve for the best device fabricated from the PbAc 2 route measured under simulated AM 1.5G (100 mW cm À 2 ) solar irradiation in air, exhibiting outstanding 3% when scanned from SC to FB, so far among the highest efficiencies based on CH 3 NH 3 PbI 3 with a PHJ structure 5,7,10,26 . The hysteresis between forward and backward J-V scan is a manifestation of a slow response time of the cell to a change in load and the mechanism, although yet to be fully understood, is discussed in detail in recent publications 35,36 . The best means to compare cells that exhibit hysteresis is to measure the 'stabilized power output' under load near the maximum power point.…”
Section: Resultsmentioning
confidence: 99%
“…7b the J-V curve for the best device fabricated from the PbAc 2 route measured under simulated AM 1.5G (100 mW cm À 2 ) solar irradiation in air, exhibiting outstanding 3% when scanned from SC to FB, so far among the highest efficiencies based on CH 3 NH 3 PbI 3 with a PHJ structure 5,7,10,26 . The hysteresis between forward and backward J-V scan is a manifestation of a slow response time of the cell to a change in load and the mechanism, although yet to be fully understood, is discussed in detail in recent publications 35,36 . The best means to compare cells that exhibit hysteresis is to measure the 'stabilized power output' under load near the maximum power point.…”
Section: Resultsmentioning
confidence: 99%
“…Both the perovskite absorber layer and the interfaces between the perovskite and the charge extraction layers can have a significant impact upon the long-term stability of the solar cell. [11][12][13][14][15][16] All commercial solar modules are encapsulated in order to enable 25 years of operation. Silicon modules have historically been encapsulated with a polymer back sheet laminated with a hot-melt polymer foil to a glass front sheet, and are moving toward glass-glass laminates to deliver improved stability.…”
Section: Doi: 101002/adma201604186mentioning
confidence: 99%
“…Several authors have reported on this effect and speculated about the causes. [18][19][20][21][22] Some recent articles present cell designs that minimize this hysteresis. 23,24 In this article, we describe the hysteresis effect in additional detail.…”
Section: Introductionmentioning
confidence: 99%
“…18 All three of these possibilities remain in the debate. 5,19,20,20,25 Along with the addition of crystal size effects 21 . It has been proposed that an optimum mesoporous TiO 2 film thickness minimizes the JV hysteresis.…”
Section: Introductionmentioning
confidence: 99%